Papillary fibroelastoma of the heart - Ahuja Janhvi; Amonkar Gayathri; Deshpande Jaya (Wolters Kluwer Medknow Publications, 2008)
Primary intra-cardiac tumors are rare. Most of them are benign. Of the benign tumors, myxomas are the most common. Others are lipoma, rhabdomyoma, hemangioma, and papillary fibroelastoma (PFE). PFE is a relatively rare benign tumor of the heart. It occurs commonly on cardiac valves and is often an incidental finding. They are most commonly discovered during autopsy, but may present with thromboembolism, which is a dreaded complication. It is important to be aware of this entity because even though it is benign it may present with life-threatening complications, which are well documented in literature. Surgery is the treatment of choice for these tumors. We present the case of a 30-year-old male in whom PFE was an incidental finding